Digital marketing indicators to state public websites archives - Giroto Ferreira, Luan Henrique [UNESP]; Caldas, Rosangela Formentini [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2017)
The web as a framework for new forms of communication and informational interaction allows to enhance the archival units. The marketing adapts to digital media in order to conquer other markets with better precision and meet the audience's needs. The research is justified by the few studies of this nature in the information science field and it is believed that the results support the development of digital marketing for informational institutions. Thus it tends to be problematic the access research to information through Digital Marketing for state public archives front. The purpose of the investigative study proposed is to analyze websites of Brazilian state public records in order to verify the institutional promotion through digital marketing and informational dissemination carried out through the virtual spaces while forming an electronic environment. The study is a qualitative approach, with case study methodology of the digital environment of the information units carrying out a comparative analysis of the websites of state public archives.
Keywords: Digital marketing; Dissemination; Indicators; Archive